2019
DOI: 10.1364/boe.10.000747
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of time- and angular-domain scatter rejection in mesoscopic optical projection tomography: a simulation study

Abstract: Optical imaging offers exquisite sensitivity and resolution for assessing biological tissue in microscopy applications; however, for samples that are greater than a few hundred microns in thickness (such as whole tissue biopsies), spatial resolution is substantially limited by the effects of light scattering. To improve resolution, time-and angular-domain methods have been developed to reject detection of highly scattered light. This work utilizes a modified version of a commonly used Monte Carlo light propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Fat, which had intermediate scattering properties, therefore showed improvements between that of lymph nodes and muscle. These findings support the conclusions of the previous simulation study 26 in that angle restriction is an appropriate scatter rejection method specifically for lymph node applications because of its mesoscopic size and low scattering optical properties. While the resolution is obviously not sufficient to localize the 200-μm inclusions from these single projections, based on the aforementioned simulation, 27 it is expected that, upon tomography and reconstruction, they would be detected and localized with ease.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Fat, which had intermediate scattering properties, therefore showed improvements between that of lymph nodes and muscle. These findings support the conclusions of the previous simulation study 26 in that angle restriction is an appropriate scatter rejection method specifically for lymph node applications because of its mesoscopic size and low scattering optical properties. While the resolution is obviously not sufficient to localize the 200-μm inclusions from these single projections, based on the aforementioned simulation, 27 it is expected that, upon tomography and reconstruction, they would be detected and localized with ease.…”
supporting
confidence: 91%
“…Specifically, for objects with the size and optical properties of lymph nodes, it has been demonstrated, in absorption-based OPT simulation study, that angular restriction with a numerical aperture (NA) = 0.005 is sufficient to detect and localize 0.2mm-diameter objects. 26 While small NA is common in standard OPT to maximize depth of field, the level required for scatter rejection as demonstrated in the aforementioned study is an order of magnitude lower than what is typically used. Using the time-resolved lymph node transmittance optical property measurements and OPT system optimization (e.g., NA and associated optical components) with Monte Carlo simulation in the work done by Sinha et al, 26 study was conducted where it was demonstrated that up to 100% detectability and 95% localization of 0.2-mm micrometastases in 10-mm-diameter nodes could be achieved with FBP reconstruction.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…As well as allowing comparison between instruments and enabling the standardisation of best practice, 112 phantoms facilitate the assessment of novel or more complex experimental setups by allowing a robust assessment of any effects on image quality and quantification (for example, multiple animal scanning in preclinical studies) 113 . Consequently, reconstruction algorithms used for OPT are also discussed that include scattering 106,114,115 …”
Section: Strategies From Medical Imagingmentioning
confidence: 99%